Conformational design characterization of a truncated diamine oxidase - Razali, Nur Nadia (2014)
Diamine oxidase, DAO (EC 1.4.3.22) is an oxidoreductase enzyme that degrades primary amines to produce aldehyde, H2O2 and NH3. DAO, also known as histaminase, is a homodimer protein consisting of 60 to 105 kDa subunits. Being a large protein,DAO is more susceptible to destabilising agents such as heat and pH, similar to other large proteins. Due to the large structure of native diamine oxidase, researchers are being actively conducted to develop a more versatile, and stable protein because big molecules do not perform well in microsystem. It also gave more flexiblity and low cost in production. Thus, the aim of this study was to develop a low cost miniature version of the native protein while mimicking its catalytic function via protein engineering and biomolecular approaches. In the protein engineering approach, a rational design was applied to produce a mini protein that can offer more potential i.e. for use in the bioinformatics and biological discoveries. The gene encoding diamine oxidase was identified in the UNITPROT/KB database and it showed a 61% sequence similarity when blasted with NCBI database. The protein structure was built using a homology modeling in YASARATM . All the constituent functional domains of the protein were prescisely defined and shown as predicted. The miniaturization process of the protein was started with size reduction after its conserved domain has been predicted. Based on several observations, there were three domains in the predicted structure with each domain having its own major contribution to the protein structure. The domain 4 that contained the active site was selected for the splicing process in order to retain the enzyme’s active site. The molecular dynamic simulation study was executed within 20 ns for each of the structures. This step is important to detect any abnormality in the in silico structure. Based on results from the RMSD, SASA and RMSF it has been determined that the mini DAO has maintained its stability which is in alignment with the parental protein. The model protein was then submitted to a protein-ligand docking simulation to study the interaction between the enzyme and a substrate. The ligand interaction showed that histamine and spermidine were excellent substrates for the mini protein because they maintained the preferences of the native protein, which often chooses short-chain length substrates. Quality assessments of the native and mini protein were also conducted using several types of verification software. Subsequently, a number of model structures were generated using a biomolecular method where the native and mini protein has been successfully cloned into vector pET102/TOPO during the first stage. The transformation of the recombinant proteins was also conducted as the sequencing result was identical to the expected reference sequence. Next, the recombinant cell was expressed into E. coli BL21 (DE3) and induced with 20% of IPTG, at 25°C for 24 h. A final mini protein activity of 62.283 U/mL was determined. Crude enzyme obtained from the intracellular expression was then purified. Purification strategy for obtaining fusion mini protein with his-tagged was established. Furthermore, fusion native purification was conducted to recover the fusion protein through affinity chromatography Ni-Sepharose. High purification yield of 88% was obtained for mini protein fusion tagged (His-tagged + mature mini protein). The molecular weight of the mini protein was 42.2 kDa by SDS-PAGE. As expected, the mini protein showed a high level of interaction with histamine. Surprisingly, the mini protein had also interacted with spermidine, a long side-chain ligand, which showed that its specificity towards different substrates had broadened up. By maintaining the native protein’s pH profile, the mini protein was highly active at 40 °C and stable at pH 7, with a half-life of 80 min at 50 °C. Results from the kinetic studies showed that the Km value for native diamine oxidase was 0.274 mM and 1.3 mM for the mini protein. Based on these results, it can be concluded that the mini protein was more active than the native protein but it has kept the same interaction with histamine. This characteristic has been identified by purely rational as well as experimental combinatorial design techniques. The results have been significant to postulate that the mini protein was more stable and versatile compared to the native protein due to its size, thermostability and broad substrate specificity. This mini protein is a suitable candidate for industrial biocatalyst and biological sensor applications.